The use of technology in education (Research, Society and Development, 2023)
The objective of this study is to describe the role of technology within Education, outlining positive and negative points of its use in schools. The present investigation is characterized as a bibliographical research, of a qualitative nature, as well as being classified as a basic and exploratory research. To collect data, the search platform “Google Scholar” was used, using the descriptors “Technologies and Education”. The objective was not to establish a current state of knowledge, but to find works that discussed the topic of Technology and Education, so that, based on the views of different authors, there could be a debate on the topic. The delimitation of the searches was from 2016 to 2023. The analysis of the results took place through exclusion, separation and interpretation of the findings. Among the main results obtained, it can be said that technology has existed since the beginning of humanity, but due to the transformations that the world has undergone today, it grows and evolves rapidly, becoming part of people's daily lives and present in the most different and varied sectors of work, commerce, industries, leisure, studies, etc. It was seen that its use in education is necessary, as it is part of students' daily lives, but for its use to be effective and to provide meaningful learning, teachers need to have good training. Some positive points found are that technology can promote student learning if used as a means, it can also motivate young people and reduce time and space, one of its negative points is that in many cases it can serve as a distraction.